2022
DOI: 10.1016/j.jmoldx.2021.12.004
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Validation of Noncanonical RET Fusions in Non–Small-Cell Lung Cancer through DNA and RNA Sequencing

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…We intend to conduct further studies that include more clinical features of RET-rearranged patients and prognostic evaluations of different RET-fusion subtypes. Yes 19 [43] 2 [20] RET, rearranged during transfection; ADC, adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We intend to conduct further studies that include more clinical features of RET-rearranged patients and prognostic evaluations of different RET-fusion subtypes. Yes 19 [43] 2 [20] RET, rearranged during transfection; ADC, adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, break-apart displays low sensitivity in detecting non-canonical RET fusions (19). DNA-based NGS enables the detection of high-throughput genomic alterations and novel partners of gene rearrangement, but it fails to provide information on functional fusion transcripts (20). The main laboratory methods for RET rearrangements have not been systematically investigated and fully elucidated in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although this FAM114A1 ‐ ALK rearrangement was predicted to produce an out‐of‐frame transcript, it was not sufficient to determine that this case had no functional ALK fusion. In our previous studies, we found that cases harbouring non‐productive/out‐of‐frame ALK / RET rearrangements always have canonical fusion transcripts at the RNA level [ 10 , 23 ]. On the other hand, it is a pity that this patient did not receive ALK‐targeted therapy, so we were unable to evaluate the efficacy of ALK‐TKI in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The panel consists of 83 immunomodulatory genes ( Table S1 ). The prepared libraries were sequenced, and the sequencing data were processed as previously described [ 41 ]. Gene-level expression values were computed as transcripts per million (TPM) and normalized to Z-scores before clustering.…”
Section: Methodsmentioning
confidence: 99%